2015
DOI: 10.1007/s11274-015-1873-7
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-like protein 2 may mediate the inflammation in murine mastitis through the activation of interleukin-6 and tumour necrosis factor-α

Abstract: Mastitis is the inflammation of the mammary gland. Recent research has shown that Angiopoietin-like protein 2 (ANGPTL2) is a key inflammatory mediator. In the present study, we tested whether there is a correlation between increased ANGPTL2 expression and inflammation in response to Staphylococcus aureus in murine mastitis and the mechanisms involved. Thirty mice were divided into two groups: blank control group, challenged group. The entire infused mammary glands were removed to observe the changes of histopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Latest research has found that angiopoietin-like protein 2 (ANGPTL2) is highly expressed in human tissues of the intestine, fat, retina and heart. Furthermore, more research related to the significant high expression of ANGPTL2 in pulmonary cancer tissues, as well as distant metastasis in lung tissues and lymph nodes, has emerged, indicating that ANGPTL2 promotes pulmonary cancer cell proliferation and invasion[5-12]. The study of Teicher[13] also estimated its high expression in soft tissue sarcomas, implicating that ANGPTL2 may accelerate the progression of soft tissue sarcomas.…”
Section: Introductionmentioning
confidence: 99%
“…Latest research has found that angiopoietin-like protein 2 (ANGPTL2) is highly expressed in human tissues of the intestine, fat, retina and heart. Furthermore, more research related to the significant high expression of ANGPTL2 in pulmonary cancer tissues, as well as distant metastasis in lung tissues and lymph nodes, has emerged, indicating that ANGPTL2 promotes pulmonary cancer cell proliferation and invasion[5-12]. The study of Teicher[13] also estimated its high expression in soft tissue sarcomas, implicating that ANGPTL2 may accelerate the progression of soft tissue sarcomas.…”
Section: Introductionmentioning
confidence: 99%
“…ANGPTL2 is often associated with markers of inflammation such as CRP [ 64 , 65 ], IL-6 and TNF-α [ 4 , 66 ] and although it is not always clear which comes first, it is acknowledged that ANGPTL2 participates in a pro-inflammatory loop by being sensitive to inflammation and in turn, further promotes inflammatory pathways. In our study, ANGPTL2 methylation at CpG5 is inversely correlated with CRP.…”
Section: Discussionmentioning
confidence: 99%
“…secreted from the infiltrating bone marrow-derived macrophages mediated the expression of pro-inflammatory cytokines, including TNF-α and IL-1β, to aggravate brain injury (Amadatsu et al, 2016). In addition, ANGPTL2 potentiates the inflammatory response in mastitis and paraquat induced acute lung damage in mice (Wang et al, 2015;Yang et al, 2018).…”
Section: Angptl2 In Acute Organ Injuriesmentioning
confidence: 99%
“…For example, elevated Angptl2 is found in a mouse model of ischemia‐reperfusion induced brain injury, while in an Angptl2 ‐/‐ and wildtype bone marrow chimeric mouse model, ANGPTL2 secreted from the infiltrating bone marrow‐derived macrophages mediated the expression of pro‐inflammatory cytokines, including TNF‐α and IL‐1β, to aggravate brain injury (Amadatsu et al, 2016). In addition, ANGPTL2 potentiates the inflammatory response in mastitis and paraquat induced acute lung damage in mice (Wang et al, 2015; Yang et al, 2018).…”
Section: Angptls and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation